A case series of infantile Pompe disease at the university college hospital Ibadan Nigeria. (September 2022) - Folayan, O.S.; Agaja, O.T.; Adebayo, B.E.; Ogunkunle, O.; Omokhodion, S.I.
Abstract: Infantile Pompe disease is a Glycogen storage disease caused by acid α-1, 4 -glucosidase (GAA) enzyme deficiency. The deficiency makes lysosomal glycogen accumulate in cardiac, skeletal, and smooth muscle cells resulting in muscle weakness. Incidence of infantile Pompe disease is high in people of African ancestry, but a discrepancy seems to exist between this incidence and clinical observations. This may be explained by factors that make diagnosis difficult. Underdiagnosis may be reduced if healthcare providers have a high index of suspicion, especially in infants that fail to thrive. We report three cases of infantile Pompe disease seen in our practice and the challenges in diagnosis and treatment. Methods: We report 3 cases of infantile Pompe's disease seen in our practice and the challenges encountered in establishing a diagnosis and instituting treatment. Conclusion: Pompe disease incidence is high among people of African ancestry, but the high incidence does not reflect in clinical presentations possibly because of under-diagnosis by 1st contact doctors. Weakness, cardiomegaly or cardiomyopathy, breathing difficulty, and delayed motor milestones in a child that is failing to thrive should raise the suspicion and prompt investigation for Pompe disease using the less invasive serum GAA assay. Treatment of the disease is multidisciplinary, and reversal of ventricular hypertrophy occurs with enzyme replacement therapy, this therapy is however not easily accessible from our experience with managing the cases we have reported in this document. Highlights: Infantile Pompe disease is a Glycogen storage disease caused by a deficiency of acid α-1, 4-glucosidase enzyme that leads to an accumulation of lysosomal glycogen in cardiac, skeletal, and smooth muscle cells and subsequent weakness in these muscles with severity correlating with the available residual GAA enzyme. The incidence is high in people of African ancestry, but a discrepancy seems to exist between the incidence and clinical observations. The cost of diagnostic tests and non-availability of enzyme replacement therapy for infantile Pompe disease coupled with the low index of suspicion among healthcare providers contribute largely to the almost non-existent chance of survival in children afflicted with this condition in Nigeria and other low and middle-income countries. To our knowledge, this is the first case series on Nigerian Children with infantile Pompe disease